Tunisia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper attempts to uncover the long-term determinants of the demand for foreign exchange reserves in Tunisia. It assesses the adequacy of current and projected reserves holdings in light of the country's policy choices. The paper describes recent trends in foreign exchange reserves in Tunisia. Econometric evidence on the determinants of the demand for foreign reserves in Tunisia is presented. The results are used to forecast the desired level of reserves given Tunisia's medium-term macroeconomic framework and to draw policy implications.